A new family of 1D, 2D and 3D frameworks aggregated from Ni5, Ni4 and Ni7 building units: synthesis, structure, and magnetism. Issue 22 (16th May 2016) - Liu, Ya-Hui; Lu, Li-Ping; Zhu, Miao-Li; Feng, Si-Si; Su, Feng
Abstract : Three polynuclear nickel(ii ) complexes with 1D, 2D and 3D structures are controlled by carboxylate bridges of biphenyl-3, 4′, 5-tricarboxylic acid. Magnetic studies reveal that the polymers have ferromagnetic coupling features for1 and2 and an alternating magnetic chain behavior for3 . Abstract : Three new Ni(ii )-clusters based on a Y-shaped ligand (biphenyl-3, 4′, 5-tricarboxylate, H3 BPT), [Ni5 (HBPT)4 (OH)2 (H2 O)12 ] n (1 ), [Ni4 (BPT)2 (OH)2 (H2 O)6 ] n ·4 n H2 O (2 ), and [Ni7 (BPT)2 (1, 4-bib)2 (OH)6 (HCO2 )2 ] n ·3 n H2 O (3 ) (1, 4-bib = 1, 4-bi(1 H -imidazol-1-yl)benzene), have been synthesized under solvothermal conditions. They were studied by infrared spectroscopy (IR), single crystal X-ray diffraction, thermogravimetric analysis (TGA), and magnetochemistry. The complexes contain low nuclear Ni-clusters as building units (BUs). Structurally, in1, the cluster BUs of [Ni5 (μ3 -OH)2 ] 8+ can be viewed as two reverse triangles sharing a common vertex, which are connected by the partially deprotonated μ2 –η 1 :η 1 -HBPT 2− forming 1D chains. The BUs of [Ni4 (μ3 -OH)2 ] 6+ clusters in2 can be considered as two reverse triangles sharing a common edge and extended by deprotonated μ6 –η 1 :η 1 :η 1 :η 1 :η 2 -BPT 3− constructing a 2D framework. The 3D framework of complex3 consists of a [Ni7 (μ3 -OH)4 (R-COO)7 (HCO2 )3 ] cluster BUs with fully deprotonated μ5 –η 1 :η 1 :η 1 :η 1 :η 1 :η 1 -BPT 3− and 1, 4-bib ligands. In addition, TGA reveals that the complexes are stable in the range of 293–548 K. Magnetostructural analyses indicate ferromagnetic coupling of J 1 = 1.85(3) and J 2 = 2.25(4) cm −1 in1 and J = 5.76(6) cm −1 in2, whereas magnetic parameters J 1 = −2.64(3), J 2 = −23.22(19) and J 3 = 12.02(5) cm −1 indicate an alternating magnetic chain (AF/F) in3 .